2012
DOI: 10.7903/cmr.7996
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Absorptive Capacity and Decision Speed on Organizational Innovation: A Study of Organizational Structure as an Antecedent Variable

Abstract: Following the dimensions of organizational structure and organizational innovation, this paper aims to discuss how organizational structure affects organizational absorptive capacity and decision speed, and subsequently influences organizational innovation. Based on the sample of 260 enterprises with 1282 valid questionnaires, the empirical method, using the Structural Equations Model showed the following. (1) The higher the degree of organizational formalization, the stronger the absorptive capacity of the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 63 publications
2
38
0
3
Order By: Relevance
“…Previous research confirmed that a centralized R&D structure can extend the architectural knowledge -the knowledge about how different perspectives can be integrated - (Henderson & Clark, 1990), but there is little research on this issue in the context of absorptive capacity (Zhang et al, 2007). Jansen et al (2005) indicated that improved coordination increases a firm's absorptive capacity (see also Chen & Chang, 2012b;Lopez & Esteves, 2013). This can be achieved through centralized R&D departments as they facilitate inter-divisional communication and knowledge flows.…”
Section: Centrality Of Randdmentioning
confidence: 99%
“…Previous research confirmed that a centralized R&D structure can extend the architectural knowledge -the knowledge about how different perspectives can be integrated - (Henderson & Clark, 1990), but there is little research on this issue in the context of absorptive capacity (Zhang et al, 2007). Jansen et al (2005) indicated that improved coordination increases a firm's absorptive capacity (see also Chen & Chang, 2012b;Lopez & Esteves, 2013). This can be achieved through centralized R&D departments as they facilitate inter-divisional communication and knowledge flows.…”
Section: Centrality Of Randdmentioning
confidence: 99%
“…54 More recently, Chen and Chang looked at 260 organizations via survey and determined that a high degree of organizational formalization slows decision speeds and organizational innovation. 55 Formalization is not the only predictor of change in organizations, but it does align with the restructuring phase of Rogers's innovation decision-making process. 56…”
Section: Formalizing Scholarly Communication Work With Datamentioning
confidence: 99%
“…In 1981, Howard looked at four university libraries and found that the rate of innovation is negative for centralized, formal, and stratified organizations. More recently, Chen and Chang (2012) looked at 260 organizations via survey and determined that a high degree of organizational formalization slows decision speeds and organizational innovation. Formalization is not the only predictor of change in organizations, but it does align with the restructuring phase of Rogers' (2003) innovation decision-making process.…”
Section: Innovation In Organizationsmentioning
confidence: 99%